A randomized controlled trial on rehabilitation through caregiver-delivered nurse-organized service programs for disabled stroke patients in rural china (the RECOVER trial): design and rationale. Issue 7 (October 2016) - Yan, Lijing L; Chen, Shu; Zhou, Bo; Zhang, Jing; Xie, Bin; Luo, Rong; Wang, Ninghua; Lindley, Richard; Zhang, Yuhong; Zhao, Yi; Li, Xian; Liu, Xiao; et al.
Rationale: Stroke is the leading cause of death and disability in rural China. For stroke patients residing in resource-limited rural areas, secondary prevention and rehabilitation are largely unavailable, and where present, are far below evidence-based standards. Aim: This study aims to develop and implement a simplified stroke rehabilitation program that utilizes nurses and family caregivers for service delivery, and evaluate its feasibility and effectiveness in rural China. Methods and design: This 2-year randomized controlled trial is being conducted in 2–3 county hospitals located in northwest, northeast, and southwest China. Eligible and consenting stroke inpatients (200 in total) have been recruited and randomized into either a control or intervention group. Nurses in the county hospital are trained by rehabilitation specialists and in turn train the family caregivers in the intervention group. They also provide telephone follow-up care three times post discharge. The recruitment, baseline, intervention, follow-up care, and evaluation are guided by the RECOVER mobile phone app specifically designed for this study. Study outcome: The primary outcome is patients' Barthel Index (activities of daily living: mobility, self-care, and toileting) at 6 months. Process and economic evaluation will also be conducted. Discussion: The results of our study will generate initial high-quality evidence to improve stroke care in resource-scarce settings. If proven effective, this innovative care delivery model has the potential to improve the health and function of stroke patients, relieve caregiver burden, guide policy-making, and advance translational research in the field of stroke care.